2019
DOI: 10.22159/ijpps.2020v12i1.35914
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Phytochemical Screening, Total Phenol and Flavonoid Content of Mimosa Rubicaulis and Reinwardita Indica

Abstract: Objective: Phytochemicals as phenol and flavonoid have a powerful biological activity. So, this study aimed to carry out phytochemical screening, total phenol and flavonoid content in two plant species i.e. M. rubicaulis and R. indica. Methods: The extraction of different parts of two plant species was done by maceration using ethanol. Phytochemical screening was done to confirm the presence of phytochemicals. Total phenol content was done by Folin ciocalteu method and total flavonoid content was done by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Ascorbic acid showed the lowest IC 50 value and maximum scavenging activity in comparison to the extracts and fractions. Several reports indicated that the phenolic content of the plant extracts had the reducing power of bioactive compounds and associated antioxidant activity [14][15][16][17][18]. The reducing power (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ascorbic acid showed the lowest IC 50 value and maximum scavenging activity in comparison to the extracts and fractions. Several reports indicated that the phenolic content of the plant extracts had the reducing power of bioactive compounds and associated antioxidant activity [14][15][16][17][18]. The reducing power (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The TPC was determined, as described by Gurung . 20 μg of samples were taken and added to 1 mL of DW in 15 mL falcon tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Gallic acid was taken as a standard drug for the estimation of total phenol content in citrus fruits. Folin-Ciocalteu method was used for the determination of total phenol content according to the method of [ 18 ] with some modifications. The total phenol content was expressed as mg of GAE (gallic acid equivalent) per g dry extract weight using the calibration curve of gallic acid from the standard solution of gallic acid, 50 mg/l, 100 mg/l, 200 mg/l, 300 mg/l, 400 mg/l, and 500 mg/l.…”
Section: Methodsmentioning
confidence: 99%
“…Quercetin was used as standard, and flavonoid content was determined and expressed as quercetin equivalent from the calibration curve of the dilutions of 50 mg/l, 100 mg/l, 200 mg/l, 300 mg/l, 400 mg/l, and 500 mg/l. The total flavonoid content of various fruits extract was determined by aluminum chloride complex-forming assay as described previously by [ 18 ], with some modifications. In brief, 1 ml of the sample solution was mixed with 4 ml of distilled water.…”
Section: Methodsmentioning
confidence: 99%